Perception of Students of Indonesian Language Study Program on Learning at E-Learning Sisfo Universitas PGRI Palembang - Masnunah, Masnunah; Wandiyo, Wandiyo; Aradea, Riswan (Graduate Program Magister Manajemen Pendidikan, 2022)
Learning during a pandemic or epidemic period, face-to-face learning has now become a lesson for the virtual world. From these problems online learning is one solution in carrying out the teaching and learning process, but online learning is not as easy as imagined, and there are many obstacles in learning, especially when providing material, there are several obstacles that make the learning process less effective and efficient. At PGRI University Palembang, learning through cyberspace is called SISFO E-Learning learning. The purpose of this study, based on the formulation of the problem above, is to find out student perceptions of online learning at SISFO E-Learning at PGRI Palembang University during the Covid-19 pandemic for the 2020-2021 academic year even semester. Based on the conclusions from the six indicators, namely in the form of affinity indicating the High category, thinking reflection showing the High category, interaction showing the High category, teacher support showing the High category, level support showing the High category and interpretation showing the High category of the six indicators, the average percentage is 77.33% in the High category.